Natural course of congenital hypothyroidism by dual oxidase 2 mutations from the neonatal period through puberty. Issue 4 (April 2016) - Maruo, Yoshihiro; Nagasaki, Keisuke; Matsui, Katsuyuki; Mimura, Yu; Mori, Asami; Fukami, Maki; Takeuchi, Yoshihiro
Abstract : Aim: We previously reported that biallelic mutations in dual oxidase 2 ( DUOX2 ) cause transient hypothyroidism. Since then, many cases with DUOX2 mutations have been reported. However, the clinical features and prognosis of individuals with DUOX2 defects have not been clarified. Objective: We investigated the prognosis of patients with congenital hypothyroidism (CH) due to DUOX2 mutations. Patients: Twenty-five patients were identified by a neonatal screening program and included seven familial cases. Their serum TSH values ranged from 18.9 to 734.6 mU/l. Twenty-two of the patients had low serum free thyroxine (fT4 ) levels (0.17–1.1 ng/dl). Twenty-four of the patients were treated withL -thyroxine. Methods: We analyzed the DUOX2, thyroid peroxidase, Na + /I − symporter, and dual oxidase maturation factor 2 genes of these 25 patients by PCR-amplified direct sequencing. An additional 11 genes were analyzed in 11 of the 25 patients using next-generation sequencing. Results: All patients had biallelic DUOX2 mutations, and seven novel alleles were detected. Fourteen of the patients were able to discontinue replacement therapy, and seven were receiving reducedL -thyroxine doses. Normalization of thyroglobulin lagged several years behind the completion of treatment. Two patients showed permanent hypothyroidism. Except for one case of a learning disability, growth and psychomotor development were normal. Conclusion: The prognosis of Japanese patients with DUOX2 defects was usually transient CH. Delayed improvement of thyroglobulin indicates that these patients have subclinical hypothyroidism. Hypothyroidism did not recur in patients during the study period (up to 18 years old).